2020
DOI: 10.1021/acs.iecr.9b06067
|View full text |Cite
|
Sign up to set email alerts
|

Preconcentration and Determination of Trace Hg(II) Using a Cellulose Nanofiber Mat Functionalized with MoS2 Nanosheets

Abstract: Molybdenum disulfide (MoS 2 ) nanoparticles were hydrothermally synthesized onto the surface of a cellulose nanofiber mat and demonstrated for the selective extraction and preconcentration of trace Hg(II) from aqueous media. Immobilization of MoS 2 onto solid support restricts sorbent loss during a column operation. The surface morphology and chemical bonding of the prepared material were characterized by scanning electron microscopy, tunneling electron microscopy, and X-ray photoelectron microscopy. The selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…The removal, separation, and detection of Hg(II) from aqueous solutions using MoS 2based composites were reviewed herein. 9,205,206,224,225,230,231 Ai et al first used MoS 2 as the adsorbent to remove Hg(II) in 2016. 224 The excellent mercury uptake capacity (2506 mg/ g) and large distribution coefficient (2.53 × 10 8 mL/g) was due to the wider interlayer spacing (Figure 7A).…”
Section: Removal Of Hg(ii)mentioning
confidence: 99%
See 2 more Smart Citations
“…The removal, separation, and detection of Hg(II) from aqueous solutions using MoS 2based composites were reviewed herein. 9,205,206,224,225,230,231 Ai et al first used MoS 2 as the adsorbent to remove Hg(II) in 2016. 224 The excellent mercury uptake capacity (2506 mg/ g) and large distribution coefficient (2.53 × 10 8 mL/g) was due to the wider interlayer spacing (Figure 7A).…”
Section: Removal Of Hg(ii)mentioning
confidence: 99%
“…206 Hassen et al found the low limit of detection MoS 2 for Hg(II) (0.09 μg/L). 225 Fausey et al demonstrated that MoS 2 -based fibers via bottom-up methods showed fast removal equilibrium (0.436 min −1 mg −1 ) and high Hg 0 removal capacity (6258.7 mg/g). 231 The removal mechanism between 2D MoS 2 -based and Hg(II) has been investigated by many researchers.…”
Section: Removal Of Hg(ii)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although all these techniques have several advantages such as, low detection limit, multi-elemental analysis, large dynamic linear range, high sample throughput, however, direct determination of trace heavy metal ions with complex sample matrices, such as environmental water samples is still challenging due to matrix interferences. [11][12][13] Therefore, a sample extraction and preconcentration techniques are the prerequisite step to eliminate any matrix components and consequently improving the detection limit are of signicant importance.…”
Section: Introductionmentioning
confidence: 99%
“…Modern analytical techniques such as X-ray fluorescence, atomic absorption spectrometry, inductively coupled plasma atomic emission spectrometry, and inductively coupled plasma mass spectrometry have been widely used for the analysis of Hg(II) [ 9 , 10 , 11 ]; however, direct determination of Hg(II) in real aqueous samples is challenging due to their low concentrations and complexity of sample matrices [ 12 ]. Therefore, preliminary extraction and preconcentration steps are often necessary before instrumental determination.…”
Section: Introductionmentioning
confidence: 99%